View Single Post
Old 2020-02-24, 20:40   #7
Jul 2014

3×149 Posts


Are you substituting \(e^{-u}\) for \(x\) ? What are you doin with \(u\)?

Also, in case there's an obvious remedy to my latex not parsing properly, here's an example of what I wrote in the first post without the \\( and \\).

\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}

Last fiddled with by wildrabbitt on 2020-02-24 at 20:44 Reason: needed to access page source
wildrabbitt is offline   Reply With Quote